A microplate-based DCFH-DA assay for the evaluation of oxidative stress in whole semen. Issue 9 (September 2022) - Benedetti, Serena; Catalani, Simona; De Stefani, Silvia; Primiterra, Mariangela; Fraternale, Alessandra; Palma, Francesco; Palini, Simone
Abstract: Aims: The well-documented relationship between sperm oxidation and male infertility strongly encourages the development of assays for reactive oxygen species detection in semen samples. The present study aims to apply the microplate-based 2', 7'-dichlorofluorescein diacetate assay to the evaluation of oxidative stress in unprocessed whole semen, thus avoiding sample centrifugations and other manipulations that may cause significant reactive oxygen species increments. Main methods: The fluorescence assay consisted in the quantification of both intracellular and extracellular reactive oxygen species levels in unwashed semen specimens by using the probe 2', 7'-dichlorofluorescein diacetate into a 96-well plate. The method was useful for the preliminary assessment of the oxidation levels of whole semen samples from men undergoing standard sperm analysis as well as to evaluate the effect of some pro-glutathione molecules on semen oxidative status. Key findings: The 2', 7'-dichlorofluorescein diacetate assay was successfully adapted to the evaluation of oxidative stress in whole semen, effectively revealing the perturbation of the redox homeostasis of the sample. Accordingly, specimens with abnormal sperm parameters (n = 10) presented oxidation indexes significantly higher than those with normospermia (n = 10) [7729 (range 3407–12769) vs. 1356 (range 470–2711), p < 0.001]; in addition, semen oxidation indexes negatively correlated to sperm motility and morphology. Noteworthy, whole semen exposure to pro-glutathione compounds led to reduced semen oxidation levels and sperm protection against oxidative damage. Significance: Based on our pilot experimental data, the microplate-based 2', 7'-dichlorofluorescein diacetate assay appears to be a convenient method for the detection of reactive oxygen species levels in whole semen samples, avoiding artifacts due to semen centrifugation steps. At the same time, the test could be a helpful tool for the basic and quick screening of antioxidant molecules able to preserve semen quality. Abstract : 2', 7'-dichlorofluorescein diacetate; Male infertility; Microplate fluorescence reader; Oxidative stress; Pro-glutathione molecules; Reactive oxygen species; Unwashed whole semen.